The features of SST field and large-scale front’s structure on the South Indian Ocean surface in the regions with bottom configuration inhomogeneities - E. A. Skripaleva (Ukrainian Antarctic Journal, 2013)
On the base of monthly averaged SST satellite data (AVHRR Ocean Pathfіnder Data JPL NOAA/NASA) the space-time variability of SST field and large-scale fronts on the South Indian Ocean surface is investigated in the regions with pronounced bottom configuration inhomogeneities. Shown, that the structure and characteristics of climatic seasonal cycle of SST field and hydrological fronts have the regional features above the Kerguelen ridge, Crozet plateau, Australian-Antarctic rise and others bottom relief forms.